Study of some heavy elements of Lake AL wand water in Khanaqin city in Diyala province - Khalid, Khaled Khairuddin; Seed, Ibrahim Omar (Journal of natural sciences, life and applied sciences, 2019)
This study was conducted on the waters of Lake Al-Wand and parts of the Al-wand River within Diyala province southeast of Khanaqin city 6 km from the Iraqi-Iranian border, five main sites were taken by the eight stations of the first and fifth sites on the river Al-Wand before entering the water and leaving the lake with one station for each site respectively. The second, third and fourth sites were on Lake Al-Wand with six stations and two deep depths, The study started from May 2018 to April 2019 and included the four seasons, the measurement of some heavy metals such as nickel, chrome, cobalt, and cadmium, If measured at a rate of three times and depending on the method followed by the American public health and its concentrations within the limits allowed by Iraqi and international standards.